ChemInform Abstract: Catalytic Enantioselective Synthesis of Halocyclopropanes. Issue 36 (August 2016) - Pons, Amandine; Ivashkin, Pavel; Poisson, Thomas; Charette, Andre B.; Pannecoucke, Xavier; Jubault, Philippe
Abstract: Cyclopropanation of 2‐haloalkenes with α‐cyano‐diazoacetates in the presence of a chiral Rh‐catalyst provides a general synthesis of highly functionalized cyclopropanes such as (III) and (V).